PENINGKATAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN METODE PEMBERIAN LEMBAR TUGAS SISWA PADA MATERI EKOSISTIM SISWA KELAS VII 2 SMP NEGERI 2 DUMAI - Sajarotunnur ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
This study aims to improve student learning outcomes by applying the method VII.2 class assignment sheet giving students conducted in March and April 2016. Subjects were seventh grade students of SMP Negeri 2 Dumai totaling 26 students. The parameters in this study is the absorption and mastery learning as well as student activities and teacher activities as supporting data. The research instrument used is the study and data collection instruments. The device consists of a learning syllabus, lesson plan, test, observation of student activity sheets, activity sheets teacher observation. The survey results revealed absorption of students in the first cycle is 70% with moderate category and second cycle increased to 78% in the high category. Mastery learning of students in the first cycle is 88.46% and 88.50% in the second cycle students completed. Activities of students in the first cycle an average of 80.76%% (very good) and the second cycle is an increase of 97.5% (excellent). It can be concluded that the method of administration of the student assignment sheet can improve student learning outcomes in the classroom ecosystem VII 2 material SMP Negeri 2 Dumai.